Late Quaternary changes in moisture availability and weathering intensity on the central Tibetan Plateau indicated by chemical signatures of ostracod shells - Börner, Nicole; Jochum, Klaus Peter; Stuhr, Marleen; Abstein, Michelle; Plessen, Birgit; Frenzel, Peter; Wang, Junbo; Zhu, Liping; Schwalb, Antje (Frontiers in Earth Science, 2022)
High-resolution multi-proxy records from two lakes on the southern Tibetan Plateau, Nam Co and Tangra Yumco, are used to infer long-term variations in the Asian monsoon system with a novel set of ostracod shell chemistry proxies. We track the moisture evolution since the Last Glacial Maximum using the trace element, rare earth element (REE) and stable isotope composition of ostracod shells. The sediment records covering the past 18.8 cal. ka BP and 17.4 cal. ka BP, respectively, demonstrate the suitability of REEs as indicators of weathering intensity and thus hydrological changes and moisture sources in the catchment. In Nam Co, high concentrations of light REEs between 14 to 13 cal. ka BP suggest an increased drainage from the glaciated Nyainqêngtanglha Mountains in the south, pointing to meltwater input. REEs in ostracod shells therefore provide additional information on water sources critical for the interpretation of stable isotope records. Mg/Ca, Sr/Ca and Ba/Ca ratios reflect salinity and thus changes in effective moisture. Asynchronous behavior of Mg/Ca, Sr/Ca and Ba/Ca ratios are controlled by changes in dominance of precipitating carbonate minerals in the lake. Synchronous behavior reflects calcite precipitation, indicating low-Mg/Ca warm-wet conditions. Constantly low Sr/Ca ratios reflect aragonite precipitation, indicating high-Mg dry conditions. Increased Sr/Ca and Ba/Ca relative to Mg/Ca ratios show monohydrocalcite precipitation, indicating high-Mg/Ca cold-dry conditions. Furthermore, Fe/Ca, Mn/Ca and U/Ca ratios in ostracods reflect changes in oxygen saturation in lake bottom waters controlled by lake level and microbial activity. The paleoclimate histories reconstructed from Nam Co and Tangra Yumco show high similarity throughout the late Quaternary. We identified two major dry periods, corresponding to Heinrich 1 and the Younger Dryas, followed by strengthening in Indian summer monsoon precipitation. The early Holocene is characterized by a moisture maximum, reflecting abundant water supply by a strong ISM. A time-delayed shift to dry conditions occurred at 2.6 cal. ka BP at Tangra Yumco, and at 2 cal. ka BP at Nam Co, resulting in decreasing lake levels, caused by weakened monsoon intensity due to a southeastward migration of the ISM-Westerly boundary with an estimated velocity of approximately 600 m per year.